Perencanaan Geometri Jalan Berdasarkan Metode Bina Marga Menggunakan Program Visual Basic - Prahara, Eduardi (ComTech: Computer, Mathematics and Engineering Applications, 2011)
One of the main things in a highway construction plan is the geometric design that includes horizontal and vertical alignment design. This study aims to formulate the steps of highway geometric design into Visual Basic 2005 program. The design steps are the calculation of horizontal and vertical alignment. Using Visual Basic 2005, it is expected that the calculation can be done faster than the manual calculation without mistake. The program is validated by comparing results obtained by manual calculations with a difference about 1x10-4 which is considered accurate. As a case study, a geometric road design is conducted in Bogor in 2009 with a fairly low-speed plan 20-40 km/hour. In the plan, the road has 28 PI (Points of Intersection) on the horizontal alignment and 15 PVI (Point of Vertical Intersection) and obtains good results in accordance with requirements and regulations issued by Bina Marga.